The Validity of Problem Based Learning Model To Improve Problem Solving Ability - Saragih, Sahat; ., Syafari; ., Muliyono (Advances in Social Sciences Research Journal, 2018)
The first step of this research purpose to valid the problem based learning model and the instrument problem solving ability on students of Junior High School based on curriculum 2013 in Medan city. The subject of the research was students of grade 7 State Junior High School and Private in Medan city that taken purposively random sampling, that were to select 8 Junior High School randomly with 4 State Junior High School and 4 Private Junior High School for every area in Medan town and suburb. Development Research that oriented on product developing was done by 3 steps. The first step resulted at the beginning model of the problem based learning also the instrument of problem solving ability that was the validation result of Mathematic education practioner, mathematic teacher also have been done limited try out test in the field on learning model and instrument of the research. The result was shown that the valid of learning tools to be used.